Administration of Nicotine Exacerbates the Quinine-induced Structural and Functional Alterations of Testicular Tissue in Adult Rats: An Experimental Study - Kianifard, Davoud; Mousavi Shoar, Seyyed Maysam; Aly, Ahmed; Kianifard, Leila; Rezaee, Farhad (Urology Journal, 2020)
Purpose: In this study the role of nicotine (NCT) administration on the intensity of rat testicular tissue alterations induced by quinine (QU) was evaluated. Materials and Methods: Forty adult Wistar rats were divided into four groups. Control (CON), NCT administrated (4 mg/kg) (NCT), QU treated (25 mg/kg for 7 days) (QU), and nicotine with quinine received (NCT+QU). After 28 days, serum testosterone and malondialdehyde (MDA) levels were measured. Testes and epididymides samples were prepared for determining tissue MDA levels, histomorphometry, microscopic indices of spermatogenesis, immunohistochemistry of p53 and sperm analysis. Results: Testosterone levels were decreased significantly (P = .0004) in treated groups compared to CON group. Serum MDA levels were increased significantly (P = .0004) in NCT and QU groups compared to CON group. Tissue MDA levels were increased significantly (P = .0012) in NCT+QU group in comparison to CON group. These parameters were changed significantly in NCT+QU group compared to QU group. Seminiferous tubules diameter decreased significantly (P < .0001) in treated groups compared to CON group and in NCT+QU group compared to QU group. The height of germinal epithelium decreased significantly (P = .0001) in NCT and NCT+QU groups compared to CON and QU groups. The number of Sertoli cells, spermatocytes, and spermatids decreased significantly in treated groups compared to CON group. The number of spermatogonia decreased significantly (P = .0017) in NCT and NCT+QU groups compared to CON group. The number of Sertoli cells, spermatogonia, and spermatocytes decreased significantly in NCT+QU group compared to QU group. All indices of spermatogenesis decreased in treated groups compared to CON group. The lowest mean of these indices was observed in NCT+QU group. The sperm viability decreased significantly (P < .0001) in treated groups compared to CON group. Sperm count and motility decreased significantly in NCT and NCT+QU groups compared to CON group. All experimental groups showed the over-expression of p53 compared to CON group. Conclusion: The administration of nicotine could be involved in the exacerbation of testicular tissue alterations related to quinine therapy.